Ricos e pobres no mercado de trabalho: ampliação do acesso ao ensino superior X barreiras sociais - Aline Amorim Melgaço Guimarães (2013)
The present work investigates youth transition to adulthood starting from the conclusion of higher education level up to the posterior entrance into the labor market. The work is based on a survey made by the Universidade Federal de Minas Gerais UFMG in 2006. Former students who have concluded their studies in this university in the years of 1980, 1990 and 1995 were interviewed. The main objective of this thesis is to investigate the limits and the possibilities that these former students found during their trajectories into the labor market, measured by their achieved income and occupational prestige. The study reflects upon a confrontation between meritocratic analysis and the social reproduction theory. It takes into account background and human capital variables, investigating their influence, from the point of conclusion of undergraduate level of education and trying to understand the barriers and the new possibilities in relation to intragenerational transition. The study also intends to investigate the possible effects of the conclusion of undergraduate level on the next generation by analyzing the type of schools the sons and daughters of the study sample were able to achieve. This study is relevant because it intends to investigate the rupture process or the maintaining structures of inequality that are already identified from several previous studies about social inequalities in Brazil. It is also relevant because of the contemporary context of expansion of coverage of undergraduate study level promoted by the federal government aiming to include youth who came from socially disadvantaged families and blacks into public and private universities, via the programs Reuni, Fies and ProUni. It is an investigation who intends to project possible scenarios to youth professional trajectories, investigating the achievements of the federal government in relation to social inclusion through enhancement of access to the higher education.